2022
DOI: 10.1097/cmr.0000000000000823
|View full text |Cite
|
Sign up to set email alerts
|

Robotic CyberKnife radiosurgery for small choroidal melanomas

Abstract: Plaque brachytherapy is the most common procedure for the treatment of small choroidal melanoma, especially in posteriorly located tumors. However, there is only little information on outcome after treatment with stereotactic radiosurgery, for example, CyberKnife radiosurgery. We reviewed patients with choroidal melanoma (maximum tumor height 4 mm) treated with CyberKnife radiosurgery. Demographic information, tumor dimension, complications, metastasis and overall survival during the whole follow-up were track… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Two recent studies with the longest follow-up periods have been recently published. The first study (n = 188, median follow-up = 46 months) reported metastasis in 14 patients (7.4%) 18 months after treatment (median), and survival was achieved in 178 patients (94.7%) [8]. Within the observation period, eye retention was reported in 166 68.5-84.6%) when treated with 20 Gy or less [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies with the longest follow-up periods have been recently published. The first study (n = 188, median follow-up = 46 months) reported metastasis in 14 patients (7.4%) 18 months after treatment (median), and survival was achieved in 178 patients (94.7%) [8]. Within the observation period, eye retention was reported in 166 68.5-84.6%) when treated with 20 Gy or less [7].…”
Section: Discussionmentioning
confidence: 99%
“…The use of modern RT techniques, such as stereotactic radiosurgery (SRS) or proton beam RT, promises better preservation of organs at risk. For instance, SRS and proton beam therapy have been described as effective treatments for larger choroidal melanomas [7‒9]. Here, we report on 4 patients diagnosed with medium-choroidal UM treated with CyberKnife SRS in a single session.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, MRI has had a limited role in ocular radiotherapy [139,140]. A notable exception has been stereotactic radiosurgery, where MRI is reportedly being used to complement CT imaging [141][142][143][144][145][146][147] and has shown to contribute to an increase in local control [148]. However, for other forms of ocular radiotherapy, such as brachytherapy and proton beam therapy, the therapy is planned using a dome-shaped model to approximate the tumour geometry.…”
Section: Therapy Planningmentioning
confidence: 99%